2008
DOI: 10.3748/wjg.14.2935
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic angiosarcoma manifested as recurrent hemoperitoneum

Abstract: Angiosarcoma is a rare tumor that account for less than 1% of all sarcomas. Although hepatic angiosarcoma usually presents with unspecific symptoms, it rapidly progresses and has a high mortality. We report a rare case of primary hepatic angiosarcoma manifested as recurrent hemoperitoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…Intraperitoneal haemorrhage following tumour rupture appears to be a relatively common method of acute presentation (2,4,5,14,15), usually accompanied by a high mortality risk due to exsanguination (2,4,15). Survivors usually present with a herald bleed, as in our case.…”
Section: Discussionmentioning
confidence: 74%
“…Intraperitoneal haemorrhage following tumour rupture appears to be a relatively common method of acute presentation (2,4,5,14,15), usually accompanied by a high mortality risk due to exsanguination (2,4,15). Survivors usually present with a herald bleed, as in our case.…”
Section: Discussionmentioning
confidence: 74%
“…Clinical studies that are useful for the diagnosis are ultrasounds that show the areas of heterogeneous echogenicity, sometimes with data suggesting central necrosis; in the CT, one can observe areas of hypodensity in the hepatic parenchyma,3 which may alternate with other hypodense areas corresponding to haemorrhages 13…”
Section: Discussionmentioning
confidence: 99%
“…Because of the vascular nature of such tumours, a high incidence of haemorrhage as a complication have been reported 3 5. For this reason, it is suggested that, when possible, a transjugular biopsy be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the rich vascularization of this tumor, it is not unusual to encounter spontaneous hemorrhagic complications and in 26.6% of cases the presenting sign is a hemoperitoneum, which may also recur [42,43]. Simple embolization (Fig.…”
Section: Other Primary Hemorrhagic Liver Tumorsmentioning
confidence: 96%